Qualitative Study on HIV/AIDS Prevention in Jombang City - Dwi Retno Wati; siti mudrikatin (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Background: 2022 will see an increase in the number of HIV/AIDS cases in Jombang City, ranking it second in East Java with 1388 PLWHA, 20 cases of mother-to-child HIV transmission during childbirth, 12 HIV (+) cases, 8 AIDS cases, and 100 fatalities. The Independent Practice Midwife (BPM) is the linchpin of a healthcare organization that has the potential to grow into a network of expectant mothers. Midwives are qualified to serve as health educators for expectant women who exhibit habits that increase their risk of contracting HIV/AIDS. In a qualitative study in Jombang City, the aim of this study was to determine the program to develop midwives' ability as health educators for expectant mothers in an effort to prevent HIV/AIDS transmission. Method: This study is qualitative and employs an in-depth interviewing methodology. Up to 8 stakeholders served as primary informants, while 2 NGOs and 10 BPM employees served as secondary informants. analysis of data using the content analysis approach. Results: Because national guidelines for preventing HIV transmission from mother to newborn have been popularized, stakeholders have implemented a policy that uses standard technical programs for midwifery practice. Midwives have received training in APN, PI, and STIs, but due to funding restrictions, they have never received training in HIV/AIDS counseling. There is no such thing as BPM; only the central IBI does monitoring and assessment, which is done only through monthly reports. The coordination of NGOs, KPAD Regional Child Protection Commission, Public Health Office, The Indonesian Midwives Association, and BPM in the execution of monitoring and evaluation is insufficient, and only IBI is carried out, unplanned, carried out at any moment if it is going to prolong the practice permit. BPM has not yet received special supervision. Coordination amongst stakeholders during the implementation of supervision is insufficient. In an effort to stop the spread of HIV/AIDS, health education facilities for pregnant women in BPM have been provided with posters, flipcharts, and MCH handbooks. There are four VCT clinics and three PMTCT clinics. Conclusion: Program to improve midwives' abilities as health educators for expectant mothers in an effort to stop the spread of HIV/AIDS at BPM (independent practice midwives) Jombang City. In order to improve coordination between stakeholders (KPAD Regional Child Protection Commission, Public Health Office, and IBI The Indonesian Midwives Association with BPM in monitoring and supervision, train counselors for BPM (independent practice midwives), and have midwives become more motivated to provide IEC and continue to improve professionalism in providing midwifery services, advocacy is required to the Regional/ Legislative Council